The Offspring Number of Drosophila melanogaster Meigen Consuming Monosodium Glutamate for Two Generations - Atika, Anggun Risma; Fauzi, Ahmad (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.531, 2017)
Monosodium Glutamate (MSG) is one of the flavor enhancers that most commonly used in various foods but its safety is still in doubt. In this research, a study was conducted to examine the effects of MSG administration on offspring number of Drosophila melanogaster for two generations. D. melanogaster ♂ wild-type strain was crossed with ♀ wild-type strain in glass bottle were fed with two different concentrations of 2.0% and 2.5% of MSG. Along with treated, the control flies were also set up without MSG. Based on ANOVA result, F count concentration variable on offspring number was 25.159 with the p-value 0.000 < 0.05 and F count generation variable on offspring number was 14.095 with the p-value 0.001 < 0.05. Administration of 2.0% MSG caused the increasing of offspring number but at 2.5% level, MSG caused the decreasing of offspring number. Furthermore, first-generation had a significantly higher offspring number than the second generation. The result indicated there was an accumulation of negative impacts of MSG consumption in the second generation.